Sex differences in the effects of calcitonin gene-related peptide signaling on migraine-like behavior in animal models: a narrative review - Lewter, Lakeisha A.; Arnold, Rachel L.; Narosov, Nina B.; Dussor, Gregory; Kolber, Benedict J. (Frontiers in Neurology, 2025)
Migraine is a common neurological disorder with a typical onset in adolescence or early adulthood. Migraine is three times more common in women than men, but the definitive cause underlying the observed disparity is not fully understood. Calcitonin gene-related peptide (CGRP) is a neuropeptide and potent vasodilator that is now clearly linked to migraine based on the efficacy of drugs targeting its signaling. While the efficacy and safety of drugs targeting CGRP are now well established, there is a shortage of studies exploring sex differences between CGRP and CGRP-based therapy related to migraine. This review evaluates the preclinical literature focusing on the effect of CGRP and inhibition of CGRP signaling on migraine-like behavior in male and female rodents. For this review, PubMed database was searched using the following terms: “CGRP AND Migraine AND animal models.” Papers were selected for review and risk of bias (RoB) assessment to evaluate the central question – What sex differences in CGRP signaling and migraine-like behavior are observed in rodents? CGRP itself induces pronociceptive effects in both male and female mice but when considering studies that directly compared male and females, there is a case for stronger overall effects in female rodents. Inhibition of CGRP signaling has a primarily antinociceptive effect in studies using only male or female rodents. We highlight that very few studies are conducted with adequate statistical power to measure sex differences within a single study and several studies pool mice across sexes. Given the known sex differences in the human condition, this pooling methodology may not be best practice for future studies involved CGRP in rodents. Overall, while there is clinical evidence suggesting therapeutics targeting CGRP could possibly have different gendered effects in humans, more preclinical studies need to be conducted to understand sex differences in CGRP or CGRP antagonism in migraine-like behavior.